Aromatase Inhibitors Are Associated with Low Sexual Desire Causing Distress and Fecal Incontinence in Women: An Observational Study. Issue 12 (21st October 2017) - Robinson, Penelope J.; Bell, Robin J.; Christakis, Marie K.; Ivezic, Stephanie R.; Davis, Susan R.
Abstract: Background: Little is known of the impact of aromatase inhibitor (AI) therapy on sexual and pelvic floor function. Aim: To document the prevalence of, and factors associated with, low desire, sexually related personal distress, hypoactive sexual desire dysfunction (HSDD), and pelvic floor dysfunction in women 10 years after breast cancer diagnosis. Methods: This was a prospective, observational, community-based cohort study of Australian women with invasive breast cancer recruited within 12 months of diagnosis. 1, 053 of the 1, 305 who completed the initial 5 years of study follow-up agreed to be re-contacted, and 992 of these women alive 10 years after diagnosis were sent the study questionnaire. Outcomes: The main outcome measure was HSDD determined by a score no higher than 5.0 on the desire domain of the Female Sexual Function Index (FSFI) plus a score of at least 11.0 on the Female Sexual Distress Scale–Revised (FSDS-R). Pelvic floor disorders, including urinary incontinence, fecal incontinence, and pelvic organ prolapse, were assessed using validated questionnaires. Multivariable logistic regression was used to assess factors associated with low desire, personal distress, and HSDD. Results: 625 completed questionnaires were returned. The respondents' median age was 65.1 years (range = 36.4–95.5). Current AI use was reported by 10% and tamoxifen use was reported by 3.4%. 521 of the 608 women (85.7%; 95% CI = 82.9–88.5) who competed the FSFI desire domain had low sexual desire, and 246 of the 563 women (43.7%; 95% CI = 39.6–47.8%) who completed the FSDS-R had sexually related personal distress. 221 of the 559 women (39.5%; 95% CI = 35.5–43.6%) who completed the 2 questionnaires had HSDD. Current AI users were more likely to have HSDD than non-users (55.2% [95% CI = 42.2–68.1] vs 37.8% [95% CI = 33.5–42.0]; P = .01). HSDD was more prevalent in sexually active, current AI users (66.7%; 95% CI = 49.4–83.9) vs current non-users (43.6%; 95% CI = 37.0–50.2; P = .02). In a logistic regression model, HSDD was significantly associated with current AI use and inversely associated with age. Fecal incontinence was more prevalent in AI users than in current non-users (29.8% [95% CI = 17.8–41.8] vs 16.4% [95% CI = 13.2–19.6], respectively; P = .01). Clinical Implications: It is important to address women's sexual health even many years after their breast cancer diagnosis. Strengths and Limitations: Strengths include a representative sample, use of validated questionnaires, and few missing data. Limitations include sexual activity being a 4-week recall. Conclusions: AI use is associated with HSDD and fecal incontinence in women who are 10 years after breast cancer diagnosis.